The Seismogenic Potential of the Southernmost Ryukyu Subduction Zone as Revealed by Historical Earthquakes and Slow Slip events - Chen, Sean Kuanhsiang; Wu, Yih-Min; Chan, Yu-Chang (Frontiers in Earth Science, 2022)
The southernmost Ryukyu subduction zone may have a geodetically inferred Mw 7.5 to 8.7 megathrust earthquake in a shallow locked region, the Ryukyu fault. Paleoseismological evidence of historical earthquakes available from the last 417 years indicates that only a 1920 Mw 7.7 earthquake occurred within this magnitude range, near the downdip end of the Ryukyu fault. As slow slip events downdip the locked seismogenic zone may trigger a large subduction earthquake, we investigate how the first observed slow slip events in 2005, 2009, and 2015 initiated downdip in the Ryukyu fault interface affect the occurrence of a megathrust. We establish possible megathrust earthquake cycles from Mw 7.5 to 8.7 on the Ryukyu fault using constraints from the magnitude-frequency relation based on local historical earthquakes. This analysis shows a b value of 1.2 for magnitudes greater than Mw 7.0, which is higher than the empirical 1.0 value. This indicates that the recurrence of an event up to Mw 8.7 is longer than previously thought if the megathrust events follow the observed magnitude-frequency relation. Then, we quantify the influence of slow slip events on the triggering of a potential megathrust earthquake by calculating the static stress increase. We find that stress perturbations caused by the three slow slip events are generally consistent with the values that have triggered the large interplate earthquakes in several subduction zones. However, a large earthquake has not yet been triggered on the Ryukyu fault after a sequence of slow slip events. If the 1920 Mw 7.7 earthquake is the last rupture of the Ryukyu fault, the earthquake cycle on the Ryukyu fault is very likely in an early stage. However, this is not true if the slow slip events occur toward the end of the earthquake cycle and there has been no megathrust earthquake at the fault interface in the last 417 years, as the 2011 Mw 9.0 Tohoku earthquake. Thus, higher potential for a megathrust earthquake may occur in the southernmost Ryukyu subduction zone.